Predicting body fat percentage from anthropometric measurements in asian athletes - Huang, L.; Teo, C. J. H.; Luan, Y.; Tekwe, C. D. (Journal of Science in Sport and Exercise, 2024)
Purpose Researchers have predicted body fat percentage (BF%), as indicated by dual energy X-ray absorptiometry (DXA), from skinfold thicknesses in North American and European athletes, but not athletes from other regions. We sought to estimate an equation to predict BF% in elite Asian athletes from their skinfold thickness and girth measurements, with DXA as a reference method.